PUBLIC PERCEPTION OF AIR POLLUTION IN LANDFILL-ADJACENT COMMUNITIES: THE ROLE OF SOCIO-DEMOGRAPHIC FACTORS IN URBAN INDONESIA - Simbolon, Veronika Amelia; Luh Pitriyanti; Ristina Rosauli Harianja (Bajang Institute, 2025)
Objective: This study aimed to determine the relationship between socio-demographic characteristics such as age, gender, education level, employment status, time spent at home, length of residence, and proximity to landfill with public perception of air pollution among communities living near landfill sites in urban Indonesia. Study Design: Quantitative, descriptive cross-sectional study. Place and Duration of Study: Conducted in a landfill-adjacent urban area in Tanjungpinang, Kepulauan Riau, Indonesia, from May 6 to May 8, 2024. Methodology: A total of 50 respondents aged 18 years and above were selected using purposive sampling. Data were collected through structured questionnaires assessing demographic characteristics and perceptions of air quality. Statistical analysis was conducted using descriptive statistics and chi-square tests with a significance level of p < 0.05. Results: The study found statistically significant associations between education level and perception of air pollution (p = 0.020), as well as between employment status and perception (p = 0.020). Other factors—age, gender, time spent at home, length of residence, and distance from the landfill—were not significantly associated with air pollution perception. Conclusion: Education and employment status play a key role in shaping how communities perceive air pollution near landfill sites. These findings suggest that environmental health interventions should prioritize public education and awareness programs, especially targeting individuals with lower education levels and those not engaged in formal employment.